2021
DOI: 10.3389/fsurg.2021.804137
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies to Reduce Postoperative Recurrence of Crohn's Disease After Ileocolic Resection

Abstract: Postoperative recurrence after ileocaecal resection for fibrostenotic terminal ileal Crohn's disease is a significant issue for patients as it can result in symptom recurrence and requirement for further surgery. There are very few modifiable factors, aside from smoking cessation, that can reduce the risk of postoperative recurrence. Until relatively recently, the surgical technique used for resection and anastomosis had little or no impact on postoperative recurrence rates. Novel surgical techniques such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…About one quarter of patients show an isolated involvement of the colon [ 4 ]. Based on the frequency of performed surgeries, our study population including 43.98% ileocecal resections, 35.27% right hemicolectomies and 11.57% distal colon resections is representative for this condition and aligns with previous studies [ 2 , 13 15 ].…”
Section: Discussionsupporting
confidence: 63%
“…About one quarter of patients show an isolated involvement of the colon [ 4 ]. Based on the frequency of performed surgeries, our study population including 43.98% ileocecal resections, 35.27% right hemicolectomies and 11.57% distal colon resections is representative for this condition and aligns with previous studies [ 2 , 13 15 ].…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, the "support column" that was formed maintains the shape of the original intestine and preserves a wide lumen, preventing distortions and stenosis due to recurrence. The studies considered show a low rate of surgical recurrence (0-3.4%), significantly lower especially when compared to a conventional anastomosis and an acceptable rate of post-surgical complications (Kono et al, 2011;Kono et al, 2016;Ficheira, 2021) Other positive points of this innovative surgical technique already mentioned above include preservation of blood flow and innervation, both factors associated with a high risk of anastomosis recurrence in DC (Reynolds et al, 2021;Dasharathy et al, 2021). The cumulative surgical recurrence rate at 5 and 10 years was 1.7%, with surgical recurrence occurring in only two Japanese patients (Luglio et al, 2021;Luglio et al, 2020b;) A survey by Konos et al (2015) at a center in Japan showed that the mean endoscopic recurrence score (Rutgeerts score) was i2 at 5 years after Kono-S anastomosis, which was significantly lower than in patients undergoing conventional treatment anastomotic procedures (i3).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the "support column" that was formed maintains the shape of the original intestine and preserves a wide lumen, preventing distortions and stenosis due to recurrence. The studies considered show a low rate of surgical recurrence (0-3.4%), significantly lower especially when compared to a conventional anastomosis and an acceptable rate of post-surgical complications (Kono et al, 2011;Kono et al, 2016;Ficheira, 2021) Other positive points of this innovative surgical technique already mentioned above include preservation of blood flow and innervation, both factors associated with a high risk of anastomosis recurrence in DC (Reynolds et al, 2021;Dasharathy et al, 2021). The cumulative surgical recurrence rate at 5 and 10 years was 1.7%, with surgical recurrence occurring in only two Japanese patients (Luglio et al, 2021;Luglio et al, 2020;Luglio et al, 2020b;) A survey by Konos et al (2015) at a center in Japan showed that the mean endoscopic recurrence score (Rutgeerts score) was i2 at 5 years after Kono-S anastomosis, which was significantly lower than in patients undergoing conventional treatment anastomotic procedures (i3).…”
Section: Resultsmentioning
confidence: 99%